Sustainable Campus Development in the Context of a Private Higher Education Institution in Hong Kong, a Case Study at the Hang Seng University of Hong Kong. (June 2019) - Lee, H H Y
Abstract: There was a trend of increasing private higher education institutions in Hong Kong, some higher education institutions implemented sustainable campus development despite of financial difficulties with main aim to continue the concepts and values of sustainability for the achievement of purpose of education for diffusion to the society. This paper reviewed sustainable campus development by looking at the physical environmental aspects, organizational changes and operational barriers. Moreover, different green building rating systems were discussed. It also summarized the impacts after completion of a sustainable campus development at the Hang Seng University of Hong Kong including changes in habits and behaviour, organizational re-structuring, enhancement of sustainable attributes to policy and strategic plans as well as external influences and relationships. The results demonstrated how a sustainable campus development could transform concepts, values and attitudes in relation to sustainability on individual, organizations and the society for practices.